Safety, tolerability, pharmacokinetics, and effects on human experimental pain of the selective ionotropic glutamate receptor 5 (iGluR5) antagonist LY545694 in healthy volunteers - Petersen, Karin L.; Iyengar, Smriti; Chappell, Amy S.; Lobo, Evelyn D.; Reda, Haatem; Prucka, William R.; Verfaille, Steven J. (Pain (Amsterdam), 2014)
In a 2-part study in healthy volunteers, we first established a maximally tolerated multiple dose of LY545694 of 25mg twice daily and subsequently demonstrated antihyperalgesic effect using effects in the brief thermal stimulation experimental pain model. The antihyperalgesic effect was similar to that of gabapentin. The objective of this study was to establish in healthy volunteers the maximally tolerated multiple dose (MTMD) of the ionotropic glutamate receptor 5 antagonist LY545694 (part A), and to investigate whether that dose had analgesic or antihyperalgesic effects in the brief thermal stimulation (BTS) pain model (Part B). Part A was a double-blind, placebo-controlled study in 3 groups of 10 healthy men. To simulate an extended-release formulation, study drug was administered orally over 6hours (12 equally divided aliquots at 30-minute intervals). Part B was a double-blind, placebo-controlled, double-dummy, 3-way crossover study in 27 healthy men. At each of the 3 study periods, subjects received either LY545694 (MTMD; as determined during part A) as a simulated, twice daily extended-release formulation for 4 doses over 3days, gabapentin (600mg 8hours apart; 6 doses over 3days; positive control), or matching placebo. The BTS model was induced twice with a 1-hour interval on each of the 2 study days, before drug administration and at the time of expected peak analgesia of LY545694. Plasma exposure for LY545694 was approximately linear over the 25- to 75-mg dose range. The MTMD of LY545694 was 25mg twice daily. Areas of secondary hyperalgesia were significantly smaller after administration of LY545694 and gabapentin compared with placebo (P<.0001 and P=.0004, respectively), but there was no difference between areas after administration of gabapentin and LY545694 (P=.400). Neither gabapentin nor LY545694 reduced the painfulness of skin heating during BTS model induction. The most common treatment-emergent adverse event was dizziness. The results of this study suggest that LY545694 should be explored further as a potential treatment for chronic pain involving neuronal sensitization.